2006
DOI: 10.1038/ni1406
|View full text |Cite
|
Sign up to set email alerts
|

Fever-range thermal stress promotes lymphocyte trafficking across high endothelial venules via an interleukin 6 trans-signaling mechanism

Abstract: Fever is an evolutionarily conserved response during acute inflammation, although its physiological benefit is poorly understood. Here we show thermal stress in the range of fever temperatures increased the intravascular display of two 'gatekeeper' homing molecules, intercellular adhesion molecule 1 (ICAM-1) and CCL21 chemokine, exclusively in high endothelial venules (HEVs) that are chief portals for the entry of blood-borne lymphocytes into lymphoid organs. Enhanced endothelial expression of ICAM-1 and CCL21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
256
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 196 publications
(269 citation statements)
references
References 50 publications
11
256
0
2
Order By: Relevance
“…Lymphocyte aggregates were not detected in vivo, consistent with prior observations that heat treatment alone does not induce homotypic adhesion in lymphocytes in vitro [31]. To minimize the known nonspecific effects of thermal stress on hemodynamic parameters such as vasodilatation and increased blood flow [25,26,32], which could have an impact on lymphocyte-endothelial interactions during the observation period, heated mice were allowed to revert to normothermal core temperature before adoptive transfer of fluorescent-labeled lymphocytes. Given that the velocity of noninteracting lymphocytes passing through the venular tree was similar between normothermic and hyperthermia-pretreated groups, improved lymphocyteendothelial interactions were likely due to molecular changes in the endothelium and not from nonspecific hemodynamic thermal effects [25].…”
Section: Enhanced Lymphocyte-endothelial Interactions With Hyperthermiasupporting
confidence: 83%
See 4 more Smart Citations
“…Lymphocyte aggregates were not detected in vivo, consistent with prior observations that heat treatment alone does not induce homotypic adhesion in lymphocytes in vitro [31]. To minimize the known nonspecific effects of thermal stress on hemodynamic parameters such as vasodilatation and increased blood flow [25,26,32], which could have an impact on lymphocyte-endothelial interactions during the observation period, heated mice were allowed to revert to normothermal core temperature before adoptive transfer of fluorescent-labeled lymphocytes. Given that the velocity of noninteracting lymphocytes passing through the venular tree was similar between normothermic and hyperthermia-pretreated groups, improved lymphocyteendothelial interactions were likely due to molecular changes in the endothelium and not from nonspecific hemodynamic thermal effects [25].…”
Section: Enhanced Lymphocyte-endothelial Interactions With Hyperthermiasupporting
confidence: 83%
“…In vivo homing studies also demonstrated a twofold increase in trafficking of normothermic lymphocytes to PLNs, PPs, and MLNs in mice receiving WBH. Paralleling the results of frozen section adherence assays, heat effects on homing were site specific, supported by the lack of an increase in homing to sites with normal squamous endothelial vasculature such as the liver or pancreas [25,26,32].…”
Section: Enhanced Lymphocyte-endothelial Interactions With Hyperthermiamentioning
confidence: 59%
See 3 more Smart Citations